PREVALENCE AND SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH PERIPARTUM DEPRESSION IN INDONESIA: NATIONAL BASIC HEALTH RESEARCH DATA 2018 - Rr. Arum Ariasih; Meiwita Budiharsana (IAKMI South Tangerang Branch, 2022)
Abstract Background: peripartum depression is common and causes maternal and infant morbidity if left untreated. This illness has several severity levels and onset stages that could emerge as prenatal depression, ‘baby blues’ syndrome or postpartum depression. Objective: This analysis aimed to investigate the national prevalence of depression among women in peripartum periods and its association with sociodemographic risk factors in Indonesia. Method: Data from the 2018 Ministry of Health’s cross-sectional survey that employed a multistage sampling (the 2018 Basic Health Research [Riskesdas]) were examined. Out of 8889 married or ever married women aged 15-49 years old who were pregnant and giving birth between January 1, 2017 and December 31, 2018, a total of 268 mothers was the total sample of respondents. They gave consent to respond to the modified Indonesia version of the Mini International Neuropsychiatric Interview (MINI) questionnaires for assessing the prevalence of peripartum depression. Chi-square tests and multivariate logistic regression analysis were used to determine the association between prenatal depression and participants’ characteristics. Result: Findings showed that peripartum depression included 7.9% of cases of prenatal depression and 16.4% of cases of postpartum depression. The estimated prevalence of prenatal depression was 10.2%, 7.7%, and 6.7% consecutively by the first, second and third trimesters. A statistically significant relationship was found between prenatal depression, each trimester of pregnancy and women’s educational level. Postpartum depression rates varied slightly between 15.9% (less than 2 weeks postpartum), 17.9% (2 to 4 weeks) and 16.9% (more than 4 weeks). Trimester of pregnancy, none/unfinished primary school, and not working were significantly associated with prenatal depression. Regrettably, the total of postpartum women was inadequate for multivariable analysis. Conclusion: Screening of depressive peripartum symptoms for early detection and prevention needs to be integrated into routine prenatal and postpartum care. Keywords: Peripartum Depression, Prevalence, Prenatal Depression, Postpartum Depression